Representasi Politik dan Agama dalam Film Boy From Heaven Sosiologi Sastra Alan Swingewood - Batubara, Nur Asiyah (Universitas Al Azhar Indonesia, 2026)
Boy From Heaven is a Swedish–Egyptian film directed by Tarik Saleh that explores social conflicts, particularly the interplay between politics and religion. The purpose of this study is to reveal how political and religious dynamics are represented in the power struggle. This research employs Alan Swingewood’s sociology of literature, which focuses on social issues reflected in literary works. The method used is descriptive qualitative because it allows the researcher to portray events and phenomena as they occur. The primary data source is the film Boy From Heaven by Tarik Saleh. The research findings indicate that the state carries out interventions through surveillance, manipulation, and control over religious scholars within the socio-political context. The study concludes that the film not only reflects the socio-political realities in Egypt but also criticizes the abuse of power and political interference in religious authority.Keywords - Alan Swingewood, Boy From Heaven, Politics and Religion, Representation, Sociological Literature.